2018
DOI: 10.1029/2018jb015942
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations in Earthquake Stress Drop on Gofar Transform Fault, East Pacific Rise: Implications for Fault Strength

Abstract: On Gofar Transform Fault on the East Pacific Rise, the largest earthquakes (6.0 ≤ MW ≤ 6.2) have repeatedly ruptured the same portion of the fault, while intervening fault segments host swarms of microearthquakes. These long‐term patterns in earthquake occurrence suggest that heterogeneous fault zone properties control earthquake behavior. Using waveforms from ocean bottom seismometers that recorded seismicity before and after an anticipated 2008 MW 6.0 mainshock, we investigate the role that differences in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 77 publications
(174 reference statements)
8
32
1
Order By: Relevance
“…This median is similar to or higher than other estimates on oceanic transform faults (Boettcher and Jordan, 2004;Allmann and Shearer, 2009;Moyer et al, 2018). The median stress drop is a factor of 1.7 (0.8 to 3.5) higher on the more seismically active southeast segment of the Blanco Fault.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This median is similar to or higher than other estimates on oceanic transform faults (Boettcher and Jordan, 2004;Allmann and Shearer, 2009;Moyer et al, 2018). The median stress drop is a factor of 1.7 (0.8 to 3.5) higher on the more seismically active southeast segment of the Blanco Fault.…”
Section: Discussionsupporting
confidence: 78%
“…This factor of difference should be carefully considered due to the scatter of individual stress drop, and the large uncertainty in the factor itself. Nevertheless, we note that one possible explanation for the lower stress drops on the more aseismic segment, which were also observed on the East Pacific Rise (Moyer et al, 2018), is that the more aseismic segment has higher temperatures, which lead to a shallower seismogenic zone, a shortened seismic cycle, less time for healing and thus less potential for large strength and stress drop in the earthquakes.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Yamada et al (2017) analyzed stress drops of small earthquakes off the Pacific coast of Hokkaido, Japan and found that the spatial pattern in stress drops has a good correlation with spatial characteristics of coseismic displacements during individual historical large earthquakes. Moyer et al (2018)…”
Section: Significance Of Analysis On Stress Dropmentioning
confidence: 99%